2020
DOI: 10.1177/2333794x20960264
|View full text |Cite
|
Sign up to set email alerts
|

Hematologic Profiles of Ethiopian Preterm Infants With Clinical Diagnoses of Early-Onset Sepsis, Perinatal Asphyxia, and Respiratory Distress Syndrome

Abstract: Objective. To determine the hematologic profile of preterm infants with regard to different diseases. Methods. A prospective, cross-sectional, observational study, conducted in 5 hospitals in Ethiopia from July 2016 to May 2018. Preterm babies <7 days of age were included and investigated with complete blood counts (CBC) and other investigations, accordingly. Results. Out of 4919 preterms, 3852 (78.3%) were admitted to a newborn intensive care unit, and of these, 68.3% had a CBC performed. The mean values o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…This is in agreement with Canpolat et al [18] who found an insignificant variation between both group as regards Hb and platelets count. In contrast, Tigabu et al [19] found that thrombocytopenia was found in 49.3% of patients with RDS, which is similar to research performed in Bellevue Hospital, USA and in India where they detected thrombocytopenia in 42% of newborns with RDS [20] .…”
Section: Discussionsupporting
confidence: 61%
“…This is in agreement with Canpolat et al [18] who found an insignificant variation between both group as regards Hb and platelets count. In contrast, Tigabu et al [19] found that thrombocytopenia was found in 49.3% of patients with RDS, which is similar to research performed in Bellevue Hospital, USA and in India where they detected thrombocytopenia in 42% of newborns with RDS [20] .…”
Section: Discussionsupporting
confidence: 61%
“…Haematological measurements such as the Haemoglobin (Hb) level, white blood cell (WBC) count, and platelet count are frequently used to assess preterm neonates. It is said that these quick screening tests have good sensitivity and negative predictive values and are widely available (Tigabu Kebede Z et al, 2020). Several authors have noted variations in the hematologic parameters of preterm newborns according to gestational age and birth weight (Roudil P et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Sepsis and RDS were associated with a higher eosinophil percentage, which correlated with our study in the fact that the eosinophil count significantly increased with increasing birth weight in septic neonates and with increasing gestational age in neonates with RDS (Yang J. Y. et al, 2014;Peng CT et al, 1989). Prematurity is a risk factor for neonatal sepsis, which along with anaemia, triggers infantile respiratory distress (Tigabu Kebede Z et al, 2020;Christensen R. D. et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…11 RDS accounted for a preterm newborn death rate of 12.8% in Poland, 46.9% in Nigeria, and 45% in Ethiopia. [12][13][14] Another study reported that the preterm newborn death rate in hospitals in low-resource countries ranged from 40% to 60% and the majority have only oxygen therapy. 15 However, a case fatality rate of 100% in a community-based setting was also reported.…”
Section: Introductionmentioning
confidence: 99%